A Cultural Comparative Study of Mobile Banking Adoption Factors. Issue 5 (2nd September 2020) - Changchit, Chuleeporn; Klaus, Tim; Lonkani, Ravi; Sampet, Jomjai
ABSTRACT: With the increasing popularity in smartphone usage, it is crucial for banks to offer mobile banking to allow their customers to perform banking transactions at their convenience. Banks need to understand which factors play an important role in encouraging or discouraging customers from using mobile banking. It is also important to investigate further whether bank customers' perceptions on mobile banking are influenced by culture. This study compares mobile banking perceptions between consumers in the U.S. and in Thailand. Three hundred and fifty-five (355) respondents from the U.S. and four hundred (400) respondents from Thailand participated in this study. Seven mobile banking factors predicted to influence consumers' attitude on the usage of mobile banking are investigated in this comparative study. The study finds six of these factors to be significant and also finds several factors that encourage and discourage U.S. and Thai consumers from using mobile banking.